1992
DOI: 10.1212/wnl.42.8.1532
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma glucagon in amyotrophic lateral sclerosis

Abstract: This study shown an abnormality in glucagon levels that may explain the glucose intolerance, abnormal insulin reactions, and abnormal plasma amino acid levels seen in amyotrophic lateral sclerosis (ALS). We randomly administered two test meals, differing only in protein source (soy versus casein) at least 1 week apart and measured fasting and postprandial bloods for glucagon, insulin, and glucose levels in 11 ALS patients. With the soy test meal, glucagon levels were elevated in all ALS patients compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 0 publications
4
13
0
Order By: Relevance
“…This suggests that an increase in disease severity in ALS patients is correlated with increased circulating glucagon levels. Indeed, given that impaired glucose homeostasis in ALS could occur as a consequence of higher levels of circulating glucagon [46], our data is congruent with observations that insulin resistance is related to disease severity and outcome in ALS [47].…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that an increase in disease severity in ALS patients is correlated with increased circulating glucagon levels. Indeed, given that impaired glucose homeostasis in ALS could occur as a consequence of higher levels of circulating glucagon [46], our data is congruent with observations that insulin resistance is related to disease severity and outcome in ALS [47].…”
Section: Discussionsupporting
confidence: 91%
“…As glucose intolerance and insulin resistance have been linked to ALS [24], [25], and in light of the neurotrophic and protective actions of GLP-1R activation in diverse cellular and animal models of neurodegeneration, we hypothesize that GLP-1 and analogues may provide neuroprotective actions in ALS. To test this hypothesis, we investigated the therapeutic potential of Ex-4 in both cell culture and rodent models of ALS.…”
Section: Introductionmentioning
confidence: 99%
“…In ALS, glucose intolerance and abnormal levels of glucagon, insulin and plasma amino acids have been observed [103]. Thus, while some authors support the notion that many ALS patients have some of the features of type II diabetes mellitus [104], others have shown that ALS patients are indeed hypermetabolic [105].…”
Section: Resultsmentioning
confidence: 99%